Photonic crystal-based radiative cooling semi-transparent organic photovoltaic glazing and method of making the same

CN122995395APending Publication Date: 2026-10-27BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611000912.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

目前的STOPV器件在光电转换效率(PCE)和平均可见光透过率(AVT)的平衡上已取得显著进展,但大多采用平面多层薄膜结构,器件在吸收太阳辐照发电的过程中会产生明显温升,不仅会导致光伏器件转换效率衰减,还会通过热传导加剧室内制冷能耗,现有结构普遍缺乏被动热管理与辐射制冷能力

Benefits of technology

[0023]该辐射制冷半透明有机光伏玻璃窗在保证较高可见光透光率的同时,实现了11.26%(11.26% ± 0.1%)的高功率转换效率(PCE)、34.00%的平均可见光透过率(AVT)和3.83%的最高光利用效率(LUE)。通过引入17层二氧化硅与硫化锌交替堆叠的介质型光子晶体功能层,利用多层介质膜的干涉效应实现宽光谱选择性调控,一方面在可见光波段维持高透射特性,保障建筑自然采光需求,另一方面在8-13 µm大气透明窗口波段实现高效热辐射发射,以被动辐射散热方式将器件热量辐射至深空冷源,达成零能耗被动降温效果;此外,光子晶体可调控器件内部光场分布,将部分透射光反射回活性层内部,被活性层再次吸收利用,增强可见光至红外波段的光子捕获与吸收,从而在维持高透光率的前提下有效提升器件的短路电流密度与功率转换效率。经测试,器件在大气窗口内(8-13 µm)的发射率可达87.67%,在2.5-25 µm中红外波段的发射率可达86.62%,兼具优异的光电转换性能与被动制冷能力,在建筑幕墙、窗户、采光顶等建筑光伏一体化领域具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a photonic crystal-based radiation refrigeration semi-transparent organic photovoltaic glass window and a preparation method thereof, and belongs to the technical field of building photovoltaic integration. A ternary blended active layer is used to construct a main body of a semi-transparent organic photovoltaic device, and a 17-layer dielectric photonic crystal functional layer formed by alternately stacking silicon dioxide and zinc sulfide is deposited on the surface of an ultrathin silver metal top electrode. The spectral regulation is carried out through the multilayer film interference effect of the photonic crystal, high transmittance is maintained in the visible light band to guarantee the building lighting performance, high efficient thermal radiation emission is realized in the 8-13 mu m atmospheric transparent window band, the device heat is radiated to a deep space cold source in a passive radiation heat dissipation mode, and a zero energy consumption radiation refrigeration effect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a radiation-cooled semi-transparent organic photovoltaic glass window with a photonic crystal functional layer, prepared by vacuum evaporation process, belonging to the field of building-integrated photovoltaics and optoelectronic device technology. Background Technology

[0002] With the acceleration of urbanization and the continuous rise in building energy consumption, glass curtain walls and skylights are widely used in modern buildings. While improving the lighting and aesthetic performance of buildings, they also bring serious problems of building heat gain and cooling energy consumption. Solar radiation enters the interior through building glass, significantly increasing the cooling load of air conditioning in summer. Traditional building glass only has the functions of lighting and enclosure, and cannot realize energy conversion and passive thermal control, making it difficult to meet the development requirements of ultra-low energy consumption of buildings under the dual carbon targets.

[0003] Building-integrated photovoltaics (BIPV) technology, especially semi-transparent organic photovoltaics (STOPV), is considered an effective way to balance building lighting and clean energy production. Current STOPV devices have made significant progress in balancing photoelectric conversion efficiency (PCE) and average visible light transmittance (AVT), but most employ planar multilayer thin-film structures. During the process of absorbing solar radiation to generate electricity, these devices experience significant temperature rises, which not only lead to a decrease in photovoltaic device conversion efficiency but also exacerbate indoor cooling energy consumption through heat conduction. Existing structures generally lack passive thermal management and radiative cooling capabilities.

[0004] Existing radiative cooling technologies are mostly applied to building surfaces as independent coatings or films, often at the cost of sacrificing visible light transmittance, making them unsuitable for building lighting scenarios. Existing solutions that combine radiative cooling with photovoltaic devices are usually external stacked structures, which have problems such as complex manufacturing processes, large overall thickness, and poor optical matching. Furthermore, it is difficult to achieve a balance between high transmittance, high power generation efficiency, and efficient radiative cooling at the same time, and there is a lack of integrated semi-transparent photovoltaic cooling technology solutions. Summary of the Invention

[0005] This invention proposes a radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals and its preparation method.

[0006] A translucent organic photovoltaic glass window based on photonic crystal radiation cooling is characterized by introducing a dielectric photonic crystal functional layer consisting of 17 layers of alternating silicon dioxide and zinc sulfide layers on the surface of the metal top electrode of the translucent organic photovoltaic device. The bottom and top layers of the dielectric photonic crystal functional layer are both silicon dioxide layers. By utilizing the multilayer film interference effect, a wide spectrum of selective modulation is achieved. While ensuring high visible light transmission and the optoelectronic performance of the device, the thermal emissivity of the 8-13µm atmospheric transparent window band is significantly improved, achieving zero-energy passive radiation cooling and simultaneously meeting the multiple needs of building power generation, natural lighting, and energy-saving cooling.

[0007] Furthermore, the metal top electrode is a silver electrode.

[0008] Preferably, the thickness of each layer of silicon dioxide (SiO2) is 140-160 nm, and the thickness of each layer of zinc sulfide (ZnS) is 85-100 nm.

[0009] The structure of the semi-transparent organic photovoltaic device, from bottom to top, consists of: an ITO glass substrate, a PEDOT:PSS hole transport layer, a ternary blend active layer, a PDINN electron transport layer, and a silver electrode layer.

[0010] This invention provides a method for fabricating a radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals, which is achieved through the following steps:

[0011] Step A: The active layer adopts a ternary blend system of polymer donor and dual non-fullerene acceptor. One of the wide-bandgap polymer donor materials PM6, PBDB-T, PTB7-Th, etc. (preferably PM6) and two of the small molecule non-fullerene acceptor materials BTP-eC9, L8-BO, Y6, etc. (preferably BTP-eC9 and L8-BO) are selected. The materials are accurately weighed and mixed evenly according to the preset mass ratio. The mixture is dissolved in an organic solvent and stirred thoroughly until completely dissolved to obtain the ternary blend active layer solution.

[0012] Step B: The pre-prepared ITO glass substrate is cleaned and surface treated sequentially. Then, the conjugated polymer PEDOT:PSS is spin-coated onto the ITO conductive layer as a hole transport layer. After spin-coating, thermal annealing is performed to obtain the PEDOT:PSS hole transport layer.

[0013] Step C: Spin-coat the ternary blend active layer solution prepared in step A onto the surface of the PEDOT:PSS layer obtained in step B, and anneal it under a nitrogen atmosphere to form a blend active layer film. Then cool the sample to room temperature.

[0014] Step D: Spin-coat the n-type organic semiconductor small molecule interface material PDINN as an electron transport layer on the blended active layer film obtained in step C to form a uniformly covered PDINN layer; then remove the organic functional layer of the substrate reserved anode contact area by physical scraping or solvent wiping to expose the ITO electrode;

[0015] Step E: Transfer the sample processed in step D to the vacuum evaporation chamber, align and cover the reserved anode contact area with a mask, and deposit an ultrathin silver (Ag) metal layer on the surface of the electron transport layer as a semi-transparent top electrode through a vacuum thermal evaporation process;

[0016] Step F: After the silver electrode deposition is completed, the sample is kept in a vacuum environment. After changing the evaporation source, the vacuum thermal evaporation process is continued. In the inorganic oxide medium selective emission system, silicon dioxide and zinc sulfide are used as the building blocks of the photonic crystal. The high emissivity and low refractive index silicon dioxide (SiO2) closely attached to the silver electrode is used as the first layer, and the high refractive index zinc sulfide (ZnS) is used as the second layer. The layers are alternately deposited to form a total of 17 layers of staggered stacked dielectric film system, thus constructing the photonic crystal functional layer. Finally, a semi-transparent organic photovoltaic glass window with radiation cooling characteristics is obtained.

[0017] In step A of the above-mentioned invention, the organic photovoltaic active layer solution is prepared by dissolving a ternary mixture consisting of polymer donor PM6, non-fullerene small molecule acceptor BTP-eC9, and L8-BO in an organic solvent; the mass ratio of PM6:BTP-eC9:L8-BO is 0.8:1:0.2, the solvent is chlorobenzene, or 0.5% by volume of 1,8-diiodooctane (DIO) is added as an additive; the total concentration of the solution is 17-20 mg / mL, preferably 20 mg / mL.

[0018] In step B of the above invention, after cleaning the ITO glass substrate, it is ultrasonicated twice each with deionized water, acetone, and anhydrous ethanol for 15-20 minutes each; after drying with nitrogen, it is treated with ultraviolet ozone for 15 minutes; the obtained PEDOT:PSS layer is annealed at 140-170 °C for 15 minutes; after the hole transport layer PEDOT:PSS layer is annealed, it is immediately transferred into a glove box, cooled, and then the blended active layer is prepared.

[0019] In step C of the above invention, the spin coating speed of PM6:BTP-eC9:L8-BO chlorobenzene solution is 3000 rpm and the spin coating time is 60 s; it is then baked and annealed at 100°C in a nitrogen atmosphere for 10 minutes.

[0020] In step D of the above-mentioned invention, the electron transport layer PDINN uses methanol as a solvent, the solution concentration is 1.5 mg / mL, the spin coating speed is 3000 rpm, and the spin coating time is 35 s; subsequently, the organic functional layer of the substrate reserved anode contact area is removed by physical scraping or solvent wiping to expose the ITO electrode.

[0021] In step E of the above invention, the vacuum degree is better than 3×10 -4 Evaporation was performed under Pa conditions, with the thickness of the ultrathin silver metal top electrode being 14 nm and the evaporation rate controlled at 1.0-1.5 Å / s.

[0022] In step F of the above invention, the photonic crystal functional layer is formed by alternating and cyclic deposition of silicon dioxide (SiO2) as the first layer and zinc sulfide (ZnS) as the second layer in an inorganic oxide dielectric selective emission system closely attached to the silver electrode, for a total of 17 layers. The thickness of silicon dioxide (SiO2) is 140-160 nm, and the thickness of zinc sulfide (ZnS) is 85-100 nm. The dielectric film evaporation rate is 1.0-1.5 Å / s.

[0023] This radiation-cooled semi-transparent organic photovoltaic glass window achieves a high power conversion efficiency (PCE) of 11.26% (11.26% ± 0.1%), an average visible light transmittance (AVT) of 34.00%, and a maximum light utilization efficiency (LUE) of 3.83% while maintaining high visible light transmittance. By introducing a 17-layer dielectric photonic crystal functional layer of alternating silicon dioxide and zinc sulfide layers, the interference effect of the multilayer dielectric film enables broad-spectrum selective modulation. On the one hand, it maintains high transmittance in the visible light band to ensure the building's natural lighting needs; on the other hand, it achieves efficient thermal radiation emission in the 8-13 µm atmospheric transparent window band, radiating heat from the device to a deep-space cold source through passive radiative heat dissipation, achieving a zero-energy passive cooling effect. Furthermore, the photonic crystal can modulate the internal light field distribution of the device, reflecting some transmitted light back into the active layer for reabsorption and utilization, enhancing photon capture and absorption in the visible to infrared bands. This effectively improves the short-circuit current density and power conversion efficiency of the device while maintaining high transmittance. Tests show that the device has an emissivity of 87.67% in the atmospheric window (8-13 µm) and 86.62% in the mid-infrared band (2.5-25 µm). It combines excellent photoelectric conversion performance with passive cooling capability and has broad application prospects in building photovoltaic integration fields such as building curtain walls, windows, and skylights. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the structure of the semi-transparent organic photovoltaic glass window (control sample) in this invention;

[0025] Figure 2 This is a schematic diagram of the stacked structure of the photonic crystal in this invention;

[0026] Figure 3 This is a schematic diagram of the overall structure of the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystal in this invention;

[0027] Figure 4 This is a transmission spectrum curve of the photonic crystal prepared in this invention;

[0028] Figure 5 This is a reflection spectrum curve of the photonic crystal prepared in this invention;

[0029] Figure 6 This is a comparison of the current density-voltage (JV) characteristic curves of the semi-transparent organic photovoltaic glass window in this invention and the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals.

[0030] Figure 7 This is a comparison of the transmission spectra of the semi-transparent organic photovoltaic glass window in this invention and the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals.

[0031] Figure 8 This is a comparison of the emissivity characteristic curves of the semi-transparent organic photovoltaic glass window in this invention and the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals.

[0032] Figure 9 These are the daytime temperature variation curves of the environment, the semi-transparent organic photovoltaic glass window, and the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals in this invention.

[0033] Figure 10 This is the daytime cooling temperature difference curve of the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystal in this invention, relative to the semi-transparent organic photovoltaic glass window.

[0034] Figure 11 This is the daytime cooling temperature difference curve of the semi-transparent organic photovoltaic glass window and the radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals relative to the ambient temperature in this invention. Detailed Implementation

[0035] The present invention will now be described in detail with reference to the accompanying drawings and embodiments, but the present invention is not limited to these manufacturing examples.

[0036] Example 1

[0037] This embodiment prepares a radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal. The specific preparation process is as follows: First, the semi-transparent organic photovoltaic (STOPV) unit is prepared. The etched ITO glass substrate is ultrasonically cleaned sequentially with deionized water, acetone, and anhydrous ethanol for 20 minutes each, dried with nitrogen, and then treated with ultraviolet ozone for 15 minutes. A PEDOT:PSS aqueous solution diluted with deionized water at a 1:1 volume ratio is spin-coated onto the ITO substrate at a spin speed of 2700 rpm for 40 s. The substrate is then annealed on a hot stage at 160 ℃ for 15 minutes to form a hole transport layer. After annealing, the substrate is immediately transferred to a vacuum glove box for cooling. Subsequently, in a nitrogen-atmosphere glove box, a ternary blend solution of polymer donor PM6, non-fullerene acceptor BTP-eC9, and L8-BO is prepared at a mass ratio of 0.8:1:0.2, with chlorobenzene as the solvent and a total concentration of 20%. A ternary blended active layer solution containing 0.5% (v / v) 1,8-diiodooctane (DIO) additive was spin-coated onto a PEDOT:PSS layer at 3000 rpm for 60 s, and annealed at 100°C for 10 minutes to allow the solvent to evaporate completely, forming a smooth blended active layer film. After the sample cooled to room temperature, a PDINN methanol solution (1.5 mg / mL, 3000 rpm, 35 s) was spin-coated onto the active layer film to form a uniformly covered electron transport layer. The organic functional layer in the reserved anode contact area of ​​the substrate was removed by physical scraping or solvent wiping to expose the ITO electrode. The sample was then transferred to a vacuum evaporation chamber and deposited under a vacuum level better than 3 × 10⁻⁶. -4 Under Pa conditions, the anode contact area was shielded by a mask, and a 14 nm thick layer of silver (Ag) was thermally deposited as a semi-transparent top electrode. The deposition rate was controlled at 1.0–1.5 Å / s. After the silver electrode deposition was completed, the sample was kept in a vacuum environment without breaking the vacuum. After changing the evaporation source, a vacuum thermal evaporation process was used to alternately deposit silicon dioxide (SiO2) and zinc sulfide (ZnS) dielectric films. The silicon dioxide layer, which was closely attached to the silver electrode, was used as the first layer, and the zinc sulfide layer was used as the second layer, which were alternately deposited in a cycle to form a total of 17 staggered dielectric film layers, thus constructing the photonic crystal functional layer. The photonic crystal stacking structure is shown in the figure. Figure 2 As shown in the figure; the thickness of silicon dioxide (SiO2) is 140-160 nm, the thickness of zinc sulfide (ZnS) is 85-100 nm, and the evaporation rate of the dielectric film is controlled at 1.0-1.5 Å / s. Finally, a radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal is fabricated. The overall structure of the complete device is shown in the figure. Figure 3 As shown.

[0038] Example 2

[0039] This embodiment prepares a semi-transparent organic photovoltaic glass window as a control sample. The specific preparation process is as follows: The etched ITO glass substrate was ultrasonically cleaned sequentially with deionized water, acetone, and anhydrous ethanol for 20 minutes each. After being dried with nitrogen, it was treated with ultraviolet ozone for 15 minutes. A 1:1 diluted PEDOT:PSS aqueous solution was spin-coated onto the ITO substrate at a spin speed of 2700 rpm for 40 s. The substrate was then annealed at 160 ℃ for 15 minutes to form a hole transport layer. After annealing, the substrate was immediately transferred to a vacuum glove box for cooling. Subsequently, in a nitrogen-atmosphere glove box, a ternary blend solution of polymer donor PM6, non-fullerene acceptor BTP-eC9, and L8-BO was prepared at a mass ratio of 0.8:1:0.2, with chlorobenzene as the solvent and a total concentration of 20 mg / mL, containing 0.5% by volume of 1,8-diiodooctane (DIO) additive. This solution was spin-coated at 3000 rpm for 60 minutes. The sample was coated with a PEDOT:PSS layer and annealed at 100°C for 10 minutes to allow the solvent to evaporate completely, forming a smooth blended active layer film. After the sample cooled to room temperature, a PDINN methanol solution (1.5 mg / mL, 3000 rpm, 35 s) was spin-coated onto the active layer to form an electron transport layer. The organic functional layer in the reserved anode contact area of ​​the substrate was removed by physical scraping or solvent wiping to expose the ITO electrode. The sample was then transferred to a vacuum evaporation chamber and deposited under a vacuum level better than 3 × 10⁻⁶. -4 Under Pa conditions, the anode contact area is blocked by a mask, and a 14 nm thick layer of silver (Ag) is thermally deposited as a semi-transparent top electrode. The deposition rate is controlled at 1.0-1.5 Å / s to obtain a semi-transparent organic photovoltaic glass window. The device structure is as follows: Figure 1 As shown. Under standard AM1.5G illumination conditions (100 mW / cm²), 2 Photovoltaic performance tests were conducted on a semi-transparent organic photovoltaic glass window and a radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals, respectively. The results are as follows: Figure 6 As shown. By comparing the JV characteristic curves, it can be found that the open-circuit voltage (Voc) of the planar device is 0.811 V, and the short-circuit current density (Jsc) is 20.18 mA / cm². 2 The fill factor (FF) is 61.29%, and the power conversion efficiency (PCE) is 10.03% (9.86% ± 0.17%). Furthermore, the introduction of the photonic crystal functional layer significantly improves the short-circuit current density (Jsc) to 21.81 mA / cm². 2The fill factor (FF) is 62.48%, and the optimal power conversion efficiency (PCE) reaches 11.26% (11.26% ± 0.1%). This performance enhancement is mainly attributed to the multilayer dielectric film interference effect of the photonic crystal, which reflects some of the transmitted long-wavelength light back into the active layer, extending the optical path of photons within the active layer and increasing photon capture and light absorption efficiency. This achieves improved photoelectric conversion performance while maintaining high light transmittance. Testing shows that the composite photonic crystal device simultaneously possesses an average visible light transmittance (AVT) of 34.00% and a maximum light utilization efficiency (LUE) of 3.83%, achieving a good balance between building lighting and photovoltaic power generation performance.

[0040] Example 3

[0041] This embodiment provides a comparison of the optical and thermal radiation properties of a semi-transparent organic photovoltaic glass window and a radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals, to verify the spectral modulation effect and radiation-cooling effect of the photonic crystal functional layer. Figure 4 , Figure 5 The transmission and reflection spectra of the photonic crystal shown indicate that this 17-layer dielectric photonic crystal, with alternating layers of silicon dioxide and zinc sulfide, achieves selective spectral modulation through multilayer film interference: maintaining high transmittance in the visible light band to ensure light-gathering performance, while forming a high-reflection band in the near-infrared band, which can reflect some long-wavelength photons not absorbed by the active layer back into the device, enhancing photon capture. To further verify the actual light-gathering performance of the composite device, the full-band transmission spectra of the semi-transparent organic photovoltaic glass window and the composite photonic crystal device were tested, and the results are as follows: Figure 7 As shown in the figure. A comparison reveals that after introducing the photonic crystal functional layer, the device's transmittance in the visible light band is essentially equivalent to that of a semi-transparent organic photovoltaic glass window. The overall light transmittance characteristics are not significantly impaired, ensuring natural lighting requirements in architectural settings and achieving a balance between functional expansion and light transmission performance. For the core performance of radiative cooling, the emissivity curves of the two devices in the mid-infrared band were tested, and the results are shown in the figure. Figure 8 As shown in the figure. A comparison reveals that the translucent organic photovoltaic glass window has weak infrared thermal radiation capability. However, after introducing the photonic crystal functional layer, the emissivity of the device in the 8-13 µm atmospheric transparent window band is significantly improved. This allows the device's heat to be radiated outwards through the atmospheric window in the form of long-wave thermal radiation, achieving a passive cooling effect without additional energy input. This confirms the radiative cooling function of the composite photonic crystal structure of this invention. To further verify the actual passive cooling effect of the photonic crystal functional layer, real-time temperature tests were conducted in a sunny daytime outdoor environment, covering the period from 10:00 to 22:00. The ambient temperature and the surface temperature changes of the translucent organic photovoltaic glass window and the photonic crystal-based radiative cooling translucent organic photovoltaic glass window were monitored simultaneously. The results are shown in the figure. Figure 9As shown in the figure. During the test, the ambient temperature first increased and then decreased with the solar irradiance intensity, with a daytime peak of approximately 31.6 ℃; the semi-transparent organic photovoltaic glass window accumulated heat due to the absorption of solar irradiance, with a daytime peak temperature of approximately 27.5 ℃; the device with the photonic crystal functional layer could radiate heat outward through an 8–13 µm atmospheric transparent window, with a daytime peak temperature of only approximately 22.8 ℃, and its overall operating temperature was significantly lower than that of the planar device. The real-time cooling rate of the two devices relative to the ambient temperature is shown in the figure. Figure 11 As shown in the figure, the maximum temperature reduction of the semi-transparent organic photovoltaic glass window relative to the environment is approximately 4.3 ℃, while the maximum temperature reduction of the semi-transparent organic photovoltaic glass window based on photonic crystal radiation cooling relative to the environment can reach approximately 9.2 ℃, demonstrating a significant improvement in passive cooling capacity. The real-time temperature difference between the two devices is shown in the figure. Figure 10 As shown, throughout the entire daytime testing period, the photonic crystal-based device maintained a consistently stable additional cooling effect compared to the planar device, with a temperature difference ranging from 2.5 to 4.3 °C. The maximum cooling temperature difference of approximately 4.3 °C was achieved during the midday period when solar irradiance was strongest. These results demonstrate that the photonic crystal functional layer introduced in this invention can effectively reduce the device's operating temperature under zero additional energy consumption conditions. This not only suppresses the efficiency thermal decay of photovoltaic devices but also reduces heat transfer to the interior and lowers the building's cooling load, further validating the advantages of this structure in building-integrated photovoltaics (BIPV) applications.

Claims

1. A radiation-cooled semi-transparent organic photovoltaic glass window based on photonic crystals, characterized in that, By introducing a dielectric photonic crystal functional layer consisting of 17 layers of alternating silicon dioxide and zinc sulfide on the surface of the metal top electrode of a semi-transparent organic photovoltaic device, with both the bottom and top layers being silicon dioxide layers, a wide-spectrum selective modulation is achieved using the multilayer film interference effect.

2. A radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal according to claim 1, characterized in that, The metal top electrode is a silver electrode.

3. A radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal according to claim 1, characterized in that, Each layer of silicon dioxide (SiO2) is 140-160 nm thick, and each layer of zinc sulfide (ZnS) is 85-100 nm thick.

4. A radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal according to claim 1, characterized in that, The structure of the semi-transparent organic photovoltaic device, from bottom to top, consists of: an ITO glass substrate, a PEDOT:PSS hole transport layer, a ternary blend active layer, a PDINN electron transport layer, and a silver electrode layer.

5. A method for preparing a radiation-cooled semi-transparent organic photovoltaic glass window based on a photonic crystal, as described in any one of claims 1-4, characterized in that, This can be achieved through the following steps: Step A: The active layer adopts a ternary blend system of polymer donor and dual non-fullerene acceptor. One of the wide-bandgap polymer donor materials PM6, PBDB-T, PTB7-Th, etc. (preferably PM6) and two of the small molecule non-fullerene acceptor materials BTP-eC9, L8-BO, Y6, etc. (preferably BTP-eC9 and L8-BO) are selected. The materials are accurately weighed and mixed evenly according to the preset mass ratio. The mixture is dissolved in an organic solvent and stirred thoroughly until completely dissolved to obtain the ternary blend active layer solution. Step B: The pre-prepared ITO glass substrate is cleaned and surface treated sequentially. Then, the conjugated polymer PEDOT:PSS is spin-coated onto the ITO conductive layer as a hole transport layer. After spin-coating, thermal annealing is performed to obtain the PEDOT:PSS hole transport layer. Step C: Spin-coat the ternary blend active layer solution prepared in step A onto the surface of the PEDOT:PSS layer obtained in step B, and anneal it under a nitrogen atmosphere to form a blend active layer film. Then cool the sample to room temperature. Step D: Spin-coat the n-type organic semiconductor small molecule interface material PDINN as an electron transport layer on the blended active layer film obtained in step C to form a uniformly covered PDINN layer; then remove the organic functional layer of the substrate reserved anode contact area by physical scraping or solvent wiping to expose the ITO electrode; Step E: Transfer the sample processed in step D to the vacuum evaporation chamber, align and cover the reserved anode contact area with a mask, and deposit an ultrathin silver (Ag) metal layer on the surface of the electron transport layer as a semi-transparent top electrode through a vacuum thermal evaporation process; Step F: After the silver electrode deposition is completed, the sample is kept in a vacuum environment. After changing the evaporation source, the vacuum thermal evaporation process is continued. In the inorganic oxide medium selective emission system, silicon dioxide and zinc sulfide are used as the building blocks of the photonic crystal. The high emissivity and low refractive index silicon dioxide (SiO2) closely attached to the silver electrode is used as the first layer, and the high refractive index zinc sulfide (ZnS) is used as the second layer. The layers are alternately deposited to form a total of 17 layers of staggered stacked dielectric film system, thus constructing the photonic crystal functional layer. Finally, a semi-transparent organic photovoltaic glass window with radiation cooling characteristics is obtained.

6. The preparation method according to claim 5, characterized in that, In step A, the organic photovoltaic active layer solution is prepared by dissolving a ternary mixture of polymer donor PM6, non-fullerene small molecule acceptor BTP-eC9, and L8-BO in an organic solvent; the mass ratio of PM6:BTP-eC9:L8-BO is 0.8:1:0.2, the solvent is chlorobenzene, or 0.5% by volume of 1,8-diiodooctane (DIO) is added as an additive; the total concentration of the solution is 17-20 mg / mL, preferably 20 mg / mL; In step C, the PM6:BTP-eC9:L8-BO chlorobenzene solution was spin-coated at 3000 rpm for 60 s; then baked and annealed at 100°C in a nitrogen atmosphere for 10 minutes.

7. The preparation method according to claim 5, characterized in that, In step B, after cleaning the ITO glass substrate, it is ultrasonicated twice each with deionized water, acetone, and anhydrous ethanol for 15-20 minutes each; after drying with nitrogen, it is treated with ultraviolet ozone for 15 minutes; the obtained PEDOT:PSS layer is annealed at 140-170 °C for 15 min; after the hole transport layer PEDOT:PSS layer is annealed, it is immediately transferred into a glove box, cooled, and then the blended active layer is prepared.

8. The preparation method according to claim 5, characterized in that, In step D, the electron transport layer PDINN uses methanol as a solvent, with a solution concentration of 1.5 mg / mL, a spin coating speed of 3000 rpm, and a spin coating time of 35 s; subsequently, the organic functional layer of the substrate reserved anode contact area is removed by physical scraping or solvent wiping to expose the ITO electrode; In step E, the vacuum level is better than 3×10 -4 Evaporation was performed under Pa conditions, and the thickness of the ultrathin silver metal top electrode was 14 nm, with the evaporation rate controlled at 1.0-1.5 Å / s. In step F, the photonic crystal functional layer is deposited alternately in a cycle with silicon dioxide (SiO2) as the first layer and zinc sulfide (ZnS) as the second layer in an inorganic oxide dielectric selective emission system closely attached to the silver electrode, for a total of 17 layers. The thickness of silicon dioxide (SiO2) is 140-160 nm and the thickness of zinc sulfide (ZnS) is 85-100 nm. The dielectric film evaporation rate is 1.0-1.5 Å / s.

9. The application of a photonic crystal-based radiation-cooled semi-transparent organic photovoltaic glass window as described in any one of claims 1-4, in the field of building photovoltaic integration such as building curtain walls, windows, and skylights, achieves a performance balance of high light transmittance, high power generation efficiency, and efficient radiation cooling.

10. The application according to claim 9 achieves a high power conversion efficiency (PCE) of 11.26% (11.26% ± 0.1%), an average visible light transmittance (AVT) of 34.00%, and a maximum light utilization efficiency (LUE) of 3.83%. By introducing a dielectric photonic crystal functional layer of 17 layers of alternating stacked silicon dioxide and zinc sulfide, the interference effect of the multilayer dielectric film is used to achieve wide-spectrum selective modulation. On the one hand, it maintains high transmittance characteristics in the visible light band to ensure the natural lighting requirements of buildings. The emissivity of the device reaches 87.67% in the atmospheric window (8-13 µm) and 86.62% in the mid-infrared band (2.5-25 µm).